A Rare Congenital Hand Tumour - Bhattacharya, Dr. V.; Sinha, Dr. J. K.; Tripathi, Dr. F. M.; Khanna, Dr. Mrs. S. (Indian Journal of Plastic Surgery, 1979)
A case of rare congenital hand tumour is presented.